Effects of Chinese herbal medicines on dementia risk in patients with sleep disorders in Taiwan. (10th January 2021) - Chen, Chao-Jung; Liu, Xiang; Chiou, Jian-Shiun; Hang, Liang-Wen; Li, Te-Mao; Tsai, Fuu-Jen; Ko, Cheng-Hang; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Liang, Wen-Miin; Lin, Ying-Ju
Abstract: Ethnopharmacological relevance: Sleep disorders affect an estimated 150 million people worldwide and result in adverse health, safety, and work performance-related outcomes that have important economic consequences. In Taiwan, Chinese herbal medicine (CHM) is a complementary natural medicine and has been widely used as an adjunctive therapy. Aim of the study: This study aimed to investigate the effect of CHM on dementia risk in patients with sleep disorders in Taiwan. Materials and methods: We identified 124, 605 patients with sleep disorders between the ages of 20 and 60 years. Of these, 5876 CHM users and 5876 non-CHM users were matched according to age and gender. The chi-squared test, Cox proportional hazard model, Kaplan-Meier method, and log-rank test were used for the comparisons. Association rule mining and network analysis were applied to determine a CHM pattern specialized for sleep disorders. Results: More CHM users did not use sleeping pills than non-CHM users. CHM users had a lower risk of dementia than non-CHM users after adjusting for age, gender, and sleeping pill use (hazard ratio (HR): 0.469, 95% CI = 0.289–0.760; p -value = 0.002). The cumulative incidence of dementia was lower among CHM users (long-rank test, p -value < 0.001). Association rule mining and network analysis showed that Ye-Jiao-Teng (YJT; Caulis Polygoni Multiflori ; Polygonum multiflorum Thunb ), Suan-Zao-Ren-Tang (SZRT), Jia-Wei-Xiao-Yao-San (JWXYS), He-Huan-Pi (HHP; Cortex Albizziae ; Albizia julibrissin Durazz. ), and Suan-Zao-Ren (SZR; Semen Zizyphi Spinosae ; Ziziphus jujuba Mill. ) were important CHMs for patients with sleep disorders in Taiwan. Conclusions: A comprehensive list of herbal medicines may be useful for the clinical treatment of patients with sleep disorders, and for future scientific investigations into the prevention of dementia in these patients. Graphical abstract: Image 1